An Analysis of the Effectiveness of the Special Allocation Fund (SAF) in Financing the Reconstruction of School Facilities in Bogor Regency - Anwar Razak; Ani Adiwinata Nawir; Sri Mastuti (PRESIDENSI: Jurnal Politik dan Pemerintahan, 2025)
The research focuses on the “Analysis of the effectiveness of the Special Allocation Fund (SAF) in financing the reconstruction of school facilities in Bogor Regency”. Dana Alokasi Khusus or SAF is one the Indonesian Government’s budget schemes initiated by the Ministry of Education and Culture or the MoEC to assist local governments in reconstructing school buildings that are heavily damaged due to various reasons. However, There have been an increasing number of damaged classrooms over the years during the period 2016 to 2018 in Bogor Regency, one of the worst in Indonesia. The conceptual framework was developed based on three main theoretical frameworks: the theory on measuring the effectiveness of finance policy implementation; the budget accountability in analyzing the effectiveness of public expenditure; and the currently applied government system based on decentralization policy in budget allocation in Indonesia. The research used qualitative methodology, which analyzed the collected data and information descriptively. Semi structured questionnaires were used to conduct interviews to relevant stakeholders. The implementation of building reconstruction based on allocated SAF has been both effective and ineffective. SAF scheme as one of the fiscal policy instruments under decentralization policy for improving the education quality has shown to be less effective due to miss-allocation of budget, improper distribution, lack of participation and transparency, and increased public complaint.The budget accountability of SAF in Bogor Regency has shown that policy on SAF use needs to improve. Recommendation should be directed towards policies to ensure fair process in selecting school as recipient, fair budget distribution, increased public participation and transparency